Chain Actions Generated High-Elevation and High-Relief Topography of the Eastern Margin of the Tibetan Plateau: From Deep Earth Forces to Earthquake-Induced Dams - Li, Hailong; Sun, Yujun; Zhang, Yueqiao (Frontiers in Earth Science, 2022)
High-elevation and high-relief topography is the most prominent geomorphological features of the eastern margin of the Tibetan Plateau. This paper proposes that the interaction of the endogenic and exogenic forces jointly determines the formation of such high and steep landform. Eastward propagation of the Tibetan Plateau has been portioned by NW-striking, large-scaled sinistral strike-slip faults due to resistance of rigid Yangtze craton to the east of the eastern margin of the Tibetan Plateau. The transpressional stress has emerged in eastern margin of the Tibetan Plateau and has resulted in several large-scale active faults. The transpressional behavior has changed the flowing direction of the rivers from NW-SE to nearly N-S. The transport capacity of these southward-flowing rivers decreases correspondingly. Since the late Cenozoic, intensive seismic events have occurred on the active faults of the eastern Tibetan Plateau which resulted in geohazards such as slope failures, landslides along these southward-flowing rivers. This resulted in the formation of a large number of dammed lakes in the eastern margin of the Tibetan Plateau. To a certain degree, these dammed lakes play an important role in lowering the upstream erosion rate and in accelerating downstream river incision which yields gravity unloading and uplift of the bedrock. The frequently and widely distributed damming events, therefore, forms an important supplementary factor with respect to the formation of high and steep landforms.